Exploring the reproductive toxicity and mechanism analysis of perfluorooctanoic acid and perfluorononanoic acid based on network toxicology, molecular docking, and experimental validation - Chao, Wang; Xuewen, Diao; Hao, Zhang; Shiqi, Wang; Yinuo, Zhang; Sai Hin, Lai; Wan Zurina, Wan Jaafar (Society of Environmental Toxicology and Chemistry, 2025)
This study combined network toxicology, molecular docking, and animal experiments to systematically investigate the reproductive toxicity and potential mechanisms of perfluorooctanoic acid (PFOA) and perfluorononanoic acid (PFNA). In total, 173 and 151 male infertility–related targets were identified for PFOA and PFNA, respectively, with key targets including AKT1, ESR1, EGFR, and HSP90AA1. Kyoto Encyclopedia of Genes and Genomes enrichment analysis revealed significant involvement of pathways such as phosphoinositide 3-kinase (PI3K)–protein kinase B (AKT), mitogen-activated protein kinase, and forkhead box O. Molecular docking predicted favorable binding affinities (all binding energies less than –7 kcal/mol) between each compound and the core targets, suggesting potential biological relevance. Because PFOA and PFNA share structural similarity and overlapping target profiles, PFOA was selected as the representative compound for experimental exposure. In vivo studies showed that PFOA exposure led to significant downregulated expression of PI3K, AKT, and mammalian target of rapamycin (mTOR) in mouse testes at mRNA and phosphorylation levels. Additionally, PFOA exposure caused disruptions in serum testosterone, luteinizing hormone, and follicle-stimulating hormone levels; increased oxidative stress markers (elevated malondialdehyde and reduced superoxide dismutase and glutathione); and induced sperm DNA fragmentation and morphologic abnormalities. Histological analysis revealed testicular structural damage, germ cell disorganization, and increased apoptosis. These findings demonstrate that PFOA and PFNA likely exert reproductive toxicity through interference with the PI3K/AKT/mTOR signaling pathway, leading to oxidative stress, endocrine disruption, and reduced spermatogenesis.